Impak program latihan pekerja sektor perhotelan, teknologi maklumat dan komunikasi - Abd Hair Awang; Rahmah Ismail; Zulridah Mohd Noor; Salma Hamzah (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2010)
Nurturing a high-quality, knowledgeable and innovative human capital with strong moral and ethical values has become a new source of driving the nation’s productivity growth and competitiveness. Therefore, Human Resource Development Council (HRDC) was established in 1992 to generate lifelong learning in workplace setting to enhance labor productivity, technology transfer and innovation. In 2002 it was renamed as Human Resource Development Limited (HRDL). All registered employers with HRDL are eligible for the employees training grants. The total approved training scheme and disbursement of training grants had increased over the years. This study investigates to what extent the training programs improve employee knowledge, skills, works behavior and job performance, and what are the significant training related factors influencing job and company performance. The result is based on data collected through self-administrated survey on 1000 employees (30.4 percent responded) at hotels, resorts and ICTs companies in three selected states. The result shows that in general the training programs improve knowledge, skills and positive work behavior of employees. Multiple linear regression analysis supports the hypothesis that training related variables have positive impact on employees’ job performance and company performance